Polymerization of beta-pinene with ethylaluminum dichloride (C2H5AlCl2) - Guiné, Raquel P. F. (2001)
The main goal of this work is to study the cationic polymerization of terpenes, particularly of beta-pinene, with alkylaluminum catalysts. Some experiments at different polymerization temperatures (10, 20, and 50°C) were carried out with ethylaluminum dichloride catalyst, C2H5AlCl2. From the results, it is possible to draw some general conclusions about the evolution of chain growth during polymerization. This work also includes the influence of reaction temperature on some properties of the final resin, particularly the molecular weight distribution, the softening point, and the Gardner color index. The role of reducing agents, such as iodine, during the distillation of the final resin is also evaluated with respect to color and softening point. As a result of this investigation, the Mark-Howink constants for terpene resins in toluene and dicloromethane as solvents have also been experimentally determined, thus allowing a more precise use of size exclusion chromatography in the characterization of such natural based products. © 2001 John Wiley & Sons, Inc. J Appl Polym Sci 82: 2558-2565, 2001